2-(5-Fluoro-3-methylsulfanyl-1-benzofuran-2-yl)acetic acid - Choi, Hong Dae (International Union of Crystallography, 2009)
The title compound, C(11)H(9)FO(3)S, was prepared by alkaline hydrolysis of ethyl 2-(5-fluoro-3-methylsulfanyl-1-benzofuran-2-yl)acetate. In the crystal structure, the carboxyl groups are involved in intermolecular O—H⋯O hydrogen bonds, which link the molecules into centrosymmetric dimers. These dimers are further packed into stacks along the b axis by intermolecular C—H⋯O and C—H⋯F interactions.